MANAJEMEN PERENCANAAN DAN REKRUTMEN TENAGA PENDIDIK OLEH DINAS PENDIDIKAN KOTA TERNATE - Nani I. Rajaloa; Rustam Hasyim (Universitas Khairun, 2018)
This research entitled Management Planning and Recruitment of Educators by the Education Office of Ternate City. The background of this study explains the human resources planning of the educators is the initial stage of the implementation of management functions. This planning is often overlooked. By doing this plan, all functions of human resources can be implemented effectively and efficiently. In addition, the function and role of educators are professionals in charge of planning and implementing the learning process, assessing the learning outcomes, conducting guidance and training in improving the quality of education.This research uses a naturalistic qualitative approach to describe the management of human resources educators at the official service of Ternate City comprehensively, naturally and deeply. A naturalistic qualitative approach is used to obtain information and deep interpretation of the meaning of human resource management in accordance with the reality of the field. Techniques data collection in this study is conducted through several techniques, namely observation, interview and documentation. Data collection techniques by conducting interview is to answer the provided research questions. Informants consisted of heads of education offices, principals, teachers and school committees.The conclusion of this study indicates that the planning and recruitment of Education Officers of Education Office of Ternate City has not been optimal in viewing the aspect of equal distribution of teacher placement, administration, management, development, supervision, and technical service to support education process in education unit. In addition there is still a gap of subject teachers in each school. Furthermore, many educators have not yet maximized their capability in performing their obligations as a professional teacher. Kata Kunci: Planning, Recruitment, Educators, and Education Office of Ternate City